Successful Treatment of Pneumothorax in a Dog With Sterile Pleural Fibrosis Caused by Chylothorax - Rehbein, Sina; Manchi, George; Gruber, Achim D.; Kohn, Barbara (Frontiers in Veterinary Science, 2019)
A 2-year-old, 12 kg, intact male crossbreed dog was presented with respiratory distress, exercise intolerance and gagging. Plain thoracic radiographs revealed severe pleural effusion. Although bilateral needle thoracocentesis and chest tube placement were performed, no re-expansion of the lung lobes occurred. Pleural effusion was of chylous quality and led to lung entrapment. Computer tomography revealed a highly atrophic and atelectatic right middle lung lobe. The remaining lung lobes were only expanded to approximately 40 %. Visceral pleura and pericardium showed a heterogeneous thickening consistent with pleural fibrosis. Partial pericardiectomy with resection of the middle lung lobe through a right lateral thoracotomy was performed. Ligation of the thoracic duct and ablation of the cisterna chyli was achieved through a single paracostal approach. Histopathology revealed chronic-active proliferative beginning granulomatous pleuritis, fibrotic pericarditis and partial coagulative necrosis with incomplete granulomatous sequestration in the resected middle lung lobe. Chylothorax resolved after surgical intervention. Active pleural effusion resolved, and lung entrapment changed to trapped lung disease. The remaining lung lobes re-expanded to approximately 80 % over the following six days. The dog was discharged ten days later. Mild to moderate pleural effusion of non-chylic quality was present during the following four months. Meloxicam was administered for four months because of its anti-fibrotic and anti-inflammatory properties. Fifteen months later, thoracic radiographs revealed full radiologic expansion of the lungs with persistent mild pleural fibrosis. To the authors’ knowledge, this is the first case report of pneumothorax due pleural fibrosis caused by chylothorax in a dog with an excellent clinical outcome.